Biologics as novel therapeutics for the treatment of allergy: Challenges and opportunities - Atanasio, Amanda; Orengo, Jamie M.; Sleeman, Matthew A.; Stahl, Neil (Frontiers in Allergy, 2022)
Over the last 4 decades there has been a significant global increase in the incidence and prevalence of IgE-mediated allergy. Although much progress has been made in the management of allergy via patient education, pharmacotherapy and immunomodulatory treatment regimens, significant unmet need remains. Advancements in our knowledge base surrounding the type 2 immune response, production of IgE and maintenance of immunological memory has led the field to explore targeted intervention of allergic pathways using monoclonal antibodies (mAbs). Intervention at various stages of the allergic cascade offers the opportunity to prevent initiation and/or maintenance of the type 2 immune response and effectively provide therapeutic benefit to patients. Furthermore, a better understanding of the protective mechanisms involved in allergen specific immunotherapy (AIT) has led us to appreciate the interplay of immunoglobulins in the allergic response, specifically the benefit in shifting the IgG:IgE ratio in favor of functionally relevant blocking IgG. Thus, treatments that lower IgE or boost IgG with the ability to outcompete IgE binding to allergen also present a favorable approach in the treatment of allergy. In this short review we discuss and highlight recent advances in the use of biologics to treat severe allergy, highlighting the key challenges but also the significant opportunities and advances to date.